Pembaharuan UU Perseroan Terbatas dalam Kerangka Good Corporate Governance - ery arifudin (Fakultas Hukum Universitas Islam Indonesia, 2002)
The problem of Good Govemance is as the need of the Acts innovation on Company Limited. It is aimedto orderthat either closedor openedcompanies could implement the principles of Good Govemance consistently. There are two important things needed of the innovation the Acts for Company Limited related to the principles of Good Governance, namely theproblem ofexistence for independent commissioner and the problem for financial report from a Company Limited.